An Efficient Symmetric Electrolyzer Based On Bifunctional Perovskite Catalyst for Ammonia Electrolysis. Issue 22 (8th October 2021) - Zhang, Mengfei; Li, Hao; Duan, Xiuyun; Zou, Peimiao; Jeerh, Georgina; Sun, Boyao; Chen, Shigang; Humphreys, John; Walker, Marc; Xie, Kui; Tao, Shanwen
Abstract: Ammonia is a natural pollutant in wastewater and removal technique such as ammonia electro‐oxidation is of paramount importance. The development of highly efficient and low‐costing electrocatalysts for the ammonia oxidation reaction (AOR) and hydrogen evolution reaction (HER) associated with ammonia removal is subsequently crucial. In this study, for the first time, the authors demonstrate that a perovskite oxide LaNi0.5 Cu0.5 O3‐ δ after being annealed in Ar (LNCO55‐Ar), is an excellent non‐noble bifunctional catalyst towards both AOR and HER, making it suitable as a symmetric ammonia electrolyser (SAE) in alkaline medium. In contrast, the LNCO55 sample fired in air (LNCO55‐Air) is inactive towards AOR and shows very poor HER activity. Through combined experimental results and theoretical calculations, it is found that the superior AOR and HER activities are attributed to the increased active sites, the introduction of oxygen vacancies, the synergistic effect of B‐site cations and the different active sites in LNCO55‐Ar. At 1.23 V, the assembled SAE demonstrates ≈100% removal efficiency in 2210 ppm ammonia solution and >70% in real landfill leachate. This work opens the door for developments towards bifunctional catalysts, and also takes a profound step towards the development of low‐costing and simple device configuration for ammonia electrolysers. Abstract : A non‐noble perovskite electrocatalyst, efficiently catalyzing both AOR and HER under alkaline conditions, is identified. The assembled symmetric ammonia electrolyzer based on this bifunctional catalyst delivers the ammonia removal efficiency of ≈100% in ammonia solution and over 70% in a real landfill leachate, demonstrating the huge potential for development of low‐cost and simple configuration for ammonia electrolyzer.